Dinamika Kebenaran Epistemik Keagamaan dalam Tantangan dan Pembaharuan Pada Era Penggunaan Kecerdasan Buatan - Daffa, Muhammad; Kamil, Fabhian Aliy Rajaie (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
In a period of advanced data and communication innovations, artificial intelligence (AI) has become a fundamental part of various parts of human existence. The research aims to explore artificial intelligence's impact on contemporary human religious understanding, especially on epistemic truth. This research applies a qualitative methodology to detail and understand epistemic truth in the context of religion in the era of artificial intelligence. This approach provides space for complex and contextual insights into the impact of artificial intelligence on religious understanding. Exploring religious epistemic truth involves analysing epistemological theories such as coherence, correlation and pragmatism, which provide deep insights. The main criterion of coherence theory is internal consistency, correlation theory focuses on correspondence with spiritual reality, and pragmatic theory emphasises practical impact in religious practice. The era of utilising artificial intelligence brings significant ethical concerns and social impacts. Challenges, such as the risk of bias in religious interpretation by algorithms, the potential to replace the spiritual role of humans and ethical concerns regarding privacy and data security, are issues that need attention. Therefore, this article contributes to integrating theories of religious epistemology with the modern challenges that arise with the use of artificial intelligence in religious life. The holistic approach adopted by this article provides deep insights into the complexity of truth and ethical values in the technological era.